2022
DOI: 10.1371/journal.pntd.0010861
|View full text |Cite
|
Sign up to set email alerts
|

The epidemiology and disease burden of congenital TORCH infections among hospitalized children in China: A national cross-sectional study

Abstract: Background Congenital TORCH (Toxoplasma gondii (T. gondii), rubella virus (RV), cytomegalovirus (CMV), and herpes simplex virus (HSV)) infections are associated with a variety of adverse prenatal and neonatal events, including miscarriage, malformations and developmental abnormalities, and they remain an issue that cannot be neglected in China. However, the current research focuses more on the general screening of TORCH in women of childbearing age, and the medical information of children hospitalized due to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 34 publications
0
9
0
1
Order By: Relevance
“…Beijing Children's Hospital Affiliated with Capital Medical University has undertaken an initiative to collect the FSMRs of inpatient children from 27 tertiary children's hospitals, creating the Futang Update Medical Records (FUTURE) database 15 . This database has been leveraged to publish numerous studies on diverse illnesses that affect children 10,16–19 . In this particular study, the FSMR details of children admitted with adenovirus encephalitis from the FUTURE database were gathered and organized.…”
Section: Methodsmentioning
confidence: 99%
“…Beijing Children's Hospital Affiliated with Capital Medical University has undertaken an initiative to collect the FSMRs of inpatient children from 27 tertiary children's hospitals, creating the Futang Update Medical Records (FUTURE) database 15 . This database has been leveraged to publish numerous studies on diverse illnesses that affect children 10,16–19 . In this particular study, the FSMR details of children admitted with adenovirus encephalitis from the FUTURE database were gathered and organized.…”
Section: Methodsmentioning
confidence: 99%
“…A populationbased cohort study demonstrated that the hazard of fetal DDs in cytomegalovirus infection pregnancy women was 233-fold higher than that in on-infected ones [94] . Another report on the burden of TORCH (Toxoplasma gondii, rubella virus, cytomegalovirus, herpes simplex virus) infection in newborns from China indicated that roughly 86% of rubella infected fetuses were accompanied by DD of cardiovascular system [95] . Some drugs used for antiinfection treatment (such as fluoroquinolones, tetracyclines, etc.)…”
Section: Low Temperaturementioning
confidence: 99%
“…The immunity to rubella is usually determined by detecting the rubella‐specific IgG antibody 19 . Vaccination, prompt detection, and other preventive strategies can reduce the adverse pregnancy outcomes from rubella virus infection 20,21 …”
Section: Introductionmentioning
confidence: 99%
“…19 Vaccination, prompt detection, and other preventive strategies can reduce the adverse pregnancy outcomes from rubella virus infection. 20,21 The rubella-containing vaccine has been available in China since 1993 and was introduced nationally into the Expanded Program on Immunization (EPI) in 2008. 22 Rubella vaccines are available either in monovalent formulation or in combination with other vaccines, such as against measles (MR) or measles and mumps (MMR).…”
mentioning
confidence: 99%